Peran Peer Pressure (Tekanan Teman Sebaya) dalam Membentuk Manifestasi Perilaku Bullying di Lingkungan Sekolah - Salbiyah Salbiyah; Caesaria Az Zahra; Risma Anita Puriani (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Bullying in school environments is a crucial issue that causes physical and emotional harm to victims and perpetuates cycles of aggression, with peer pressure identified as one of the main predictors. This study aims to address gaps in the literature regarding the specific role of peer pressure in shaping bullying behavior in Indonesian schools through a Systematic Literature Review (SLR) approach, analyzing 21 research articles published between 2021 and 2026 from Google Scholar. The findings indicate that adolescents with high peer pressure are 3.48 times more likely to engage in bullying, and high peer conformity contributes to 44.4% of bullying cases. However, peer influence is dual-sided—positive interactions based on empathy and mutual respect can reduce bullying behavior. The impacts of bullying include depression, anxiety, and declining academic performance in victims, as well as legal issues and difficulties in interpersonal relationships in perpetrators. The study concludes that collaboration among various stakeholders is essential to manage peer group norms and dynamics as part of culturally contextual bullying prevention efforts in Indonesia.